2015
DOI: 10.2174/1381612822666151112152335
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome sequencing in atherosclerosis: what's next?

Abstract: Cardiovascular diseases are currently a basic cause of mortality in highly developed countries. The major reason for genesis and development of cardiovascular diseases is atherosclerosis. At the present time high technology methods of molecular genetic diagnostics can significantly simplify early presymptomatic recognition of patients with atherosclerosis, to detect risk groups and to perform a family analysis of this pathology. A Next-Generation Sequencing (NGS) technology can be characterized by high product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…In western countries, where the burden of CVD is growing due to effect of CV risk factors, several studies have already shown the strongly relation of the genetic factors. However, little is known about the role of mtDNA CR mutations in development of stroke and MI [7][8][9]11,[13][14][15]17 .…”
Section: Discussionmentioning
confidence: 99%
“…In western countries, where the burden of CVD is growing due to effect of CV risk factors, several studies have already shown the strongly relation of the genetic factors. However, little is known about the role of mtDNA CR mutations in development of stroke and MI [7][8][9]11,[13][14][15]17 .…”
Section: Discussionmentioning
confidence: 99%
“…In western countries, where the burden of CVD is growing due to effect of CV risk factors, several studies have already shown the strongly relation of the genetic factors. However, little is know about the role of mtDNA CR mutations in development of stroke and MI [79,11,13,14,15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence have linked certain CVDs with specific mtDNA mutation including base substitution [611], deletions [12], duplications [13] and point or length heteroplasmy [1417] both in coding [6,9,10,12,14,15] and noncoding region [69,11,13,16,17] of mtDNA. In particular, mtDNA mutations located in CR have a potential importance since they may influence on the regulation of the mtDNA gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that next-generation sequencing (NGS) could be used to detect mitochondrial gene mutations (10). NGS is found to be more efficient, more sensitive, and more accurate (11, 12).…”
Section: Discussionmentioning
confidence: 99%